Microclimate characteristics and multi-effect analysis of facade and rooftop agriculture based on in-situ observation and meta-analysis - Li, Yazhe; Ma, Enpu; Liao, Liuwen; Li, Jiaqi; Zhu, Shuxuan; Zhang, Qiyue (Frontiers in Sustainable Food Systems, 2023)
Facade and rooftop agriculture has great potential in regulating urban local microclimate, building energy conservation and carbon emission reduction. This study aims to address the limitation that the existing studies lack multi-effect simulations of integrated implementation of facade and rooftop agriculture. It takes into account the variability and complexity of thermal coefficients in planting layers during the simulations. By analyzing in-situ observations, the study examines the regulatory impact of integrated agriculture on urban microclimate. Furthermore, it uses observed data instead of DeST temperature database data to simulate the energy-saving effect and carbon emission reduction. In order to analyse the average economic efficiency of rooftop and facade agriculture in China, the study conducts a meta-analysis of existing cases in China. The results of the study are as follows: (1) The thermal insulation efficiency of the facade and rooftop integrated agriculture varies with weather conditions and diurnal variations. It reaches the strongest (1.68℃) on sunny days and around noon. (2) The integrated implementation of facade and rooftop agriculture on a normal home building in Changsha can save a total of 12,226.30 kW•h (5%) of electricity per year, and thus reducing 2,809.26 kg of carbon emissions. (3) Based on meta-analysis and LCA calculation, the average net present value of the project in China for 40ais . The economic efficiency needs to be optimized. The results of this study reveal the ideal ecological benefits of facade and rooftop agriculture and the economic efficiency that hinders their implementation, providing a theoretical basis for building energy conservation and renovation, and the economic efficiency optimization in the regions with hot summer and cold winter.